Reflections on VET teacher education in Australia, against the backdrop of VET teacher education in Germany - Harris, Roger [Verfasser] (My University, 2019)
"The question as to why national vocational education and training (VET) systems differ generates ongoing debate. Typologies are frequently constructed around structural or political differences, yet the insightful work of Professor Thomas Deissinger has drawn our attention to the influence of historical and cultural aspects as being the critical factor underpinning VET policy and practice. lt is unsurprising that VET teacher education is also affected by history and culture since the quality of VET depends primarily on the quality of its teachers and trainers. This chapter therefore focuses on the historical and cultural factors influencing the rise and decline of Australian VET teacher preparation and professional development, with passing reference to the contrasting situation in Germany. In the mid- l 970s, VET teacher education moved from being mainly inhouse within State departments into higher education institutions. Today, there is the closure of many such degree programs in universities and the settling on the default position of the Certificate IV in Training and Education as the de facto qualification for all VET teachers and trainers. This chapter analyses what has happened, and critically questions whether Australia's VET practitioners are becoming deprofessionalised." (author's abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; P 3.2 Lehrpersonal; I 2.3.5 Australien, Ozeanien; Berufsbildungssystem; Berufsschullehrer; Lehrerausbildung; Lehrerbildung; Entberuflichung; Australien